Attitude and Proficiency Level of Grade 10 Learners in Science: Bases for An Interactive Intervention Material - Cabalbag, Marlou A. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
The broad scope of science, coupled with the potential for boredom, can impact student performance; therefore, fostering a positive attitude toward science is crucial for developing science process skills (SPS) and achieving academic success. Developing SPS through hands-on, inquiry-based learning improves students' scientific understanding and performance (Gizaw & Sota, 2020). This study aimed to enhance the SPS of Grade 10 learners using interactive intervention material. A survey design assessed their attitude toward science and SPS, while correlational analysis examined the relationship between attitudes and SPS. Spearman’s rank correlation and the independent t-test were used to analyze the data. Developmental design was employed to create the intervention material. Results showed that Grade 10 learners were proficient in all seven SPS, with mean scores ranging from 3.99 to 4.21. Inferring had the highest score (4.21), while interpreting had the lowest (3.99), indicating gaps in these skills. A significant positive correlation was found between attitude and proficiency in all skills. Since the skills fell under the proficient level and gaps existed, Sacapaño’s (2024) framework, where the least mean is considered a weakness and the highest as a strength, was used to determine which skills to target in the IIM. Communicating and interpreting, with the lowest scores, were identified for enhancement in the IIM. The validation of the IIM, with a weighted mean of 4 regarded as highly valid, suggested that the material could effectively enhance the communication and interpretation skills of Grade 10 learners in Candon City Division. Therefore, the researcher recommended adopting and incorporating the IIM into science instruction.